2021
DOI: 10.1016/j.conctc.2021.100834
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment on comedogenicity of dermatological products containing d-alpha tocopheryl acetate in Asian subjects: A double-blind randomized controlled trial

Abstract: A double-blind randomized controlled trial was used to assess the comedogenic potential of the dermatological products containing d-Alpha tocopheryl acetate. A total of 15 healthy males (20–45 years old) with prominent follicular orifices and the ability to form comedones on the upper aspect of the back were enrolled. Each participant was given pads containing 4 test products. The positive control arm received a pad containing octyl palmitate which is a reported comedogenic material. The negative control arm r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Dabei erschienen die Mikrokomedonen weicher und geschwollener und der Elastizitätsmodul der Mikrokomedonen war reduziert 40 . Zur Beurteilung der Komedogenität von topisch anwendbaren dermatologischen Produkten, die D‐alpha‐Tocopherylacetat enthalten, wurden die Veränderungen der Mikrokomedonen‐Anzahl in epidermalen Biopsien stereoskopisch ausgewertet 41 …”
Section: Nachweis Von Mikrokomedonenunclassified
“…Dabei erschienen die Mikrokomedonen weicher und geschwollener und der Elastizitätsmodul der Mikrokomedonen war reduziert 40 . Zur Beurteilung der Komedogenität von topisch anwendbaren dermatologischen Produkten, die D‐alpha‐Tocopherylacetat enthalten, wurden die Veränderungen der Mikrokomedonen‐Anzahl in epidermalen Biopsien stereoskopisch ausgewertet 41 …”
Section: Nachweis Von Mikrokomedonenunclassified
“…40 To assess the comedogenicity of dermatological topical products containing d-alpha tocopheryl acetate, the changes in the number of microcomedones were evaluated in epidermal biopsies using a stereomicroscope. 41…”
Section: Non-invasive Imaging Techniquesmentioning
confidence: 99%
“…It was found that the microcomedones appeared softer and more swollen and the elastic modulus of the microcomedones was decreased 40 . To assess the comedogenicity of dermatological topical products containing d‐alpha tocopheryl acetate, the changes in the number of microcomedones were evaluated in epidermal biopsies using a stereomicroscope 41 …”
Section: Detection Of Microcomedonesmentioning
confidence: 99%
“…Lesions may occur in an oily area in some people and in a dry area in others [13]. Acne-like inflammation of the skin caused by various factors that promote abnormal keratinization and desquamation of the follicular epithelium is called comedogenicity [5,14,15]. Initially, invisible lesions-microcomedones-may develop into clinically obvious comedones, either open or closed, within two months.…”
Section: Introductionmentioning
confidence: 99%